The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14334/wartazoa.v28i4.1875
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Insects as Feedstuff in Broiler Diet

Abstract: <p>Insect meal is an unconventional feedstuff and is expected to be an alternative protein source in broiler diet in the future, as an impact of high price and a limited supply of a fish meal. The objective of this paper is to describe the potency of insects as a feedstuff in broiler diet. Some types of insects, i.e., bees, flies, crickets, grasshoppers, termites, ants, and cockroaches have the potential to be a feedstuff protein source. Several studies reported that insect has high protein content (10.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Tenebrio molitor eats organic waste and transforms it into biodiesel . Growth of insects also produces valuable proteins to be utilized and researched in many fields. Among these insects, the black soldier fly larva (BSFL) has attracted increasing interest for dealing with organic waste. BSFL is highly capable in degrading organic waste and converting these degradations into rich nutrition resources including proteins and lipids. , Noticeably, the major conversion product produced by BSFL is a protein which is widely used in animal feeding. , …”
Section: Introductionmentioning
confidence: 57%
“…Tenebrio molitor eats organic waste and transforms it into biodiesel . Growth of insects also produces valuable proteins to be utilized and researched in many fields. Among these insects, the black soldier fly larva (BSFL) has attracted increasing interest for dealing with organic waste. BSFL is highly capable in degrading organic waste and converting these degradations into rich nutrition resources including proteins and lipids. , Noticeably, the major conversion product produced by BSFL is a protein which is widely used in animal feeding. , …”
Section: Introductionmentioning
confidence: 57%
“…The high and low metabolic energy content of a feed ingredient is influenced by the content of other nutrients, such as crude fiber content. According to Hidayat [ 22 ], the content of crude fiber in a material will affect the value of metabolic energy. The content of the metabolic energy value of a feed will affect the level of feed consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 showed that the difference in weight of chickens fed 15% BSF and commercial feed was not very significant due to the chitin content, reducing protein digestibility in broiler chickens [41]. Chitin is a polysaccharide compound that the monogastric digestive tract cannot adequately digest due to the nitrogen groups forming complex bonds with other compounds such as proteins, lipids, and minerals such as calcium [42]. Figure 2 showed that the difference in weight of chickens fed 15% BSF and commercial feed was not very significant due to the chitin content, reducing protein digestibility in broiler chickens [41].…”
Section: Feed Quality From the Use Of Bsf Larvaementioning
confidence: 99%